Global Climate change and local disturbance regimes as interacting drivers for shifting altitudinal vegetation patterns - Jentsch, Anke; Beierkuhnlein, Carl (ERDKUNDE, 2003)
Climate change will be a major driving factor for ecosystem development during the next century. It will be most prominent in areas with narrow climatic gradients such as high mountains. However, the life cycles and dispersal potential of species and the longevity of non-mobile specimen are likely to limit the adaptation to gradually but, compared to the temporal scale of ecosystems, rapidly changing environments. Communities may perform inertia to the shift of species composition and delay the development of more competitive communities on a long-term perspective. This in turn may promote a loss of biodiversity and restrictions in ecosystem functioning and resilience. Then in high mountains disturbances such as mud flows or avalanches might cause hazardous effects on human interests (land use, settlements, and infrastructure). In contrast to this perspective, we suggest in this paper that in a gradually changing climate, disturbances will contribute to a faster adaptation of communities. In a shifting environment, single disturbance events, that are part of a specific disturbance regime, can remove inertia (e.g. non-reproductive long-lived individuals) from a system and support the establishment of new species and structures. This is most important in regions where natural processes of ecosystem development predominate and ephemeral anthropogenic ecosystems are of low importance, which is generally the case in high mountains. Here agricultural land use is limited to small areas. Thus disturbances can contribute to the preservation of biodiversity and ecosystem stability.